The First Test of the New Neutron Generator at the VŠB - Technical University of Ostrava - Alexa, Petr; Uhlář, Radim (GeoScience Engineering, 2013)
The compact neutron generator MP320 (Thermo Scientific Inc.) operating on the principle of a deuterium-tritium reaction was tested before its planned application as the neutron source for the purpose of Fast Neutron Activation Analysis applications. Plates made from Al, Fe, Sn and Si were irradiated by a 14 MeV neutron beam and typical neutron induced reactions were identified.